The Role and Mechanism of Pyroptosis and Potential Therapeutic Targets in Sepsis: A Review - Zheng, Xiangtao; Chen, Weiwei; Gong, Fangchen; Chen, Ying; Chen, Erzhen (Frontiers in Immunology, 2021)
Sepsis is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. Recently was been found that pyroptosis is a unique form of proinflammatory programmed death, that is different from apoptosis. A growing number of studies have investigated pyroptosis and its relationship with sepsis, including the mechanisms, role, and relevant targets of pyroptosis in sepsis. While moderate pyroptosis in sepsis can control pathogen infection, excessive pyroptosis can lead to a dysregulated host immune response and even organ dysfunction. This review provides an overview of the mechanisms and potential therapeutic targets underlying pyroptosis in sepsis identified in recent decades, looking forward to the future direction of treatment for sepsis.